Physical Climate Science since IPCC AR4 : A brief update on new findings between 2007 and April 2010 - Rummukainen, Markku; Räisänen, Jouni; Björnsson, Halldór; Hesselbjerg Christensen, Jens (Copenhagen : Nordic Council of Ministers, 2010)
This report provides an update of the IPCC Fourth Assessment Report (AR4), focusing on the physical climate system that in the IPCC work is addressed by its Working Group I. The report considers progress in understanding of the human and natural drivers of climate change, climate observations, attribution, key climate feedback, as well as ocean acidification. Recent developments and near future prospects of climate modelling are also discussed in brief. Some of the key findings that the recent literature brings forth include: Parts of the Greenland and Antarctic ice sheets have shown rapid melt over recent years. Solar cycle effects on global temperatures are small compared to anthropogenic forcing More emerging research on the "other CO2 problem", ocean acidification Climate change may have significant effects on natural carbon sinks The report is written by four leading Nordic climate scientists: Markku Rummukainen, Jouni Räisänen, Jens Hesselbjerg Christensen and Halldór Björnsson on behalf of the Nordic ad hoc Group on Global Climate Negotiations. The Nordic ad hoc Group on Global Climate Negotiations prepares reports and studies, conducts meetings and organises conferences to support the Nordic negotiators in the UN climate negotiations. The overall aim of the group is to contribute to a global and comprehensive agreement on climate change with ambitious emission reduction commitments.